Salvia miltiorrhiza polysaccharides protect against lipopolysaccharide-induced liver injury by regulating NF-κb and Nrf2 pathway in mice. Issue 1 (1st January 2019) - Han, Chao; Wei, Yuanyuan; Wang, Xiao; Cui, Yuqing; Bao, Yongzhan; Shi, Wanyu
ABSTRACT: The current study was conducted to investigate the hepatoprotective effects of Salvia miltiorrhiza polysaccharides (SMP) against lipopolysaccharide (LPS) induced liver injury. The mice were treated with SMP first and LPS later. Results showed that SMPs significantly reduced the activities of serum alanine aminotransferase (ALT), aspartate transaminase (AST), total bilirubin (TBIL), malondialdehyde (MDA) and contents of inflammation factors and mRNA expressions in LPS induced liver injury mice. However, SMP significantly increased the contents of glutathione (GSH), Superoxide dismutase (SOD) and Total antioxidant capacity (T-AOC). SMP also downregulated the expressions of p-p65, p-IκBα, inducible nitricoxide synthase (iNOS) and improved the expression of Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) and Heme Oxygenase-1 (HO-1). The study indicates SMP protects the liver via attenuating inflammatory reactions and antioxidant effects.